The NeuroTracker System: Its role for perceptual-cognitive training of athletes and its potential impact on injury reductions and concussion management in sports - Faubert, J.; Sidebottom, L. (2021)
This paper presents a new approach for training high-level athletes` perceptual-cognitive skills. We first introduce concepts in regards to what is required by athletes to optimally process sportsrelated visual scenes at the perceptual-cognitive level and how complex that is. We then present a method of how it is possible to train this critical capacity in athletes while discussing the necessary features for a successful perceptual-cognitive training outcome. Our experience in the field with the top professional sports teams in the area of soccer, ice hockey and rugby clearly demonstrates that this capacity is highly trainable even in the highest-level athletes. A discussion follows emphasizing how we believe the NeuroTracking approach will become an integral component of athletic training with potential outcomes for profiling, recruiting, rehabilitation, game shape preparation and concussion management among others. We then conclude with thoughts on what the future holds in this regard and how such training programs could be integrated with other methods such as proprioceptive, and neuro/biofeedback training.